Working electrode for continuously monitoring glucose and preparation method thereof

By designing a working electrode with a multi-layer composite structure, the problems of poor biocompatibility and low signal stability of existing CGM products are solved, and the continuous monitoring effect of high sensitivity, long service life and low cost is achieved.

CN119534580AActive Publication Date: 2025-02-28JUJIAOXINCHUANG MEDICAL ELECTRONICS (SHANGHAI) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411739853.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing continuous glucose monitoring (CGM) products have problems such as poor biocompatibility, low signal stability, unstable bioenzyme fixation, poor selectivity and high cost, which affects the accuracy and service life of monitoring.

Method used

A working electrode with a multi-layer composite structure was designed, including a flexible base layer, a metal conductive layer, a catalytic reaction layer, a surface modification layer, a bioenzyme sensing layer and a hydrophobic semipermeable membrane layer. The biological enzymes were fixed by silanization treatment and chemical crosslinking, which increased the loading and fixation stability of the biological enzymes, and selectively controlled glucose permeability through the semipermeable membrane layer.

Benefits of technology

Continuous monitoring of glucose with high sensitivity, high stability and long service life is achieved, which significantly improves monitoring accuracy and anti-interference ability, while reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534580A_ABST
    Figure CN119534580A_ABST
Patent Text Reader

Abstract

The invention relates to the field of medical instruments, and discloses a CGM working electrode and a preparation method thereof. The working electrode comprises a flexible base layer, a metal conductive layer, a catalytic reaction layer, a surface modification layer, a biological enzyme sensing layer and a hydrophilic and hydrophobic semipermeable membrane layer which are sequentially stacked, wherein the surface modification layer forms a three-dimensional network structure on the surface of the catalytic reaction layer through silanization treatment and is used for enhancing biological enzyme immobilization; the semi-permeable membrane layer is composed of biocompatible polymers and used for selectively controlling permeation of glucose molecules. By the adoption of the technical scheme, the biocompatibility and measurement precision of the electrode are improved, the service life of the electrode is prolonged through the special structural design, and the electrode is simple in preparation process, controllable in cost and suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of medical device technology, and in particular to an electrochemical sensor technology for continuous blood glucose monitoring. Background Art

[0002] Diabetes is a metabolic disease characterized by elevated blood sugar due to insufficient insulin secretion and / or impaired insulin utilization. According to the latest epidemiological data, the prevalence of diabetes in my country has risen to 11.2% based on the WHO diagnostic criteria. So far, there is no cure for diabetes, and patients need to reduce their dependence on insulin by controlling their blood sugar levels. Therefore, blood sugar monitoring has become an important part of the daily management of diabetic patients.

[0003] Currently, there are two main methods of blood glucose monitoring in clinical practice: one is the traditional fingertip blood sampling method, which uses a blood glucose meter (BGM) for testing; the other is the emerging implantable continuous glucose monitoring system (CGM). Due to the shortcomings of fingertip blood sampling, such as strong pain and easy infection, patients usually only perform 2-3 tests a day, which is difficult to fully reflect the changes in blood glucose. In contrast, the CGM system only needs one implantation to continuously monitor for 14 days, and can provide real-time and continuous blood glucose data, so it has gradually become the preferred monitoring method for diabetic patients.

[0004] However, existing CGM products still have the following technical problems that need to be solved:

[0005] Biocompatibility issues: Existing working electrodes are mostly made of rigid substrate materials, which can cause obvious foreign body sensation and pain after implantation into the human body, affecting patient compliance;

[0006] Signal stability issues: The complex physiological environment in the human body can easily cause electrochemical interference, leading to measurement data deviation; and byproducts such as H2O2 can reduce the activity of biological enzymes, affecting the accuracy of long-term monitoring;

[0007] Bioenzyme fixation problem: Some products do not have a surface modification layer or use a conductive polymer mesh structure, which causes the bioenzyme to fall off easily and the loading amount is insufficient, shortening the service life of the electrode; some use a conductive polymer structure that also reduces the anti-interference ability, causing excessive data deviation;

[0008] Selectivity problem: The existing semipermeable membrane structure has poor selective permeability to glucose molecules and poor blocking effect on interfering substances, and is easily blocked by impurities, affecting detection performance;

[0009] Cost issue: Some products use complex structural designs and expensive materials, which leads to high manufacturing costs and is not conducive to promotion and use.

[0010] Therefore, there is an urgent need to develop a CGM working electrode with good biocompatibility, accurate measurement, long service life and simple preparation process to meet the needs of clinical applications. Summary of the invention

[0011] The purpose of the present application is to provide a working electrode for continuous glucose monitoring and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0012] The present application discloses a working electrode for continuous glucose monitoring, comprising:

[0013] Flexible base layer;

[0014] A metal conductive layer is disposed on the surface of the flexible base layer;

[0015] A catalytic reaction layer, disposed on the surface of the metal conductive layer, for catalyzing a glucose reaction;

[0016] A surface modification layer, formed on the surface of the catalytic reaction layer and presenting a three-dimensional network structure, is used to enhance the fixation of the biological enzyme;

[0017] A biological enzyme sensing layer is fixed on the surface of the surface modification layer by chemical bonding;

[0018] A hydrophilic and hydrophobic semipermeable membrane layer is disposed on the surface of the bio-enzyme sensing layer and is used to selectively control the permeation of glucose molecules;

[0019] The thickness of the flexible base layer is 0.075-0.15 mm, and the width is 0.35-0.45 mm; the thickness of the semi-permeable membrane layer is 10-40 μm.

[0020] In a preferred example, the surface modification layer is formed by silanization treatment.

[0021] In a preferred example, the flexible base layer is made of any one of polyimide (PI), polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), and polydimethylsiloxane (PDMS).

[0022] In a preferred example, the metal conductive layer is made of any one of gold, graphite, silver, titanium, iridium and ruthenium, and the thickness of the metal conductive layer is 2-30 μm.

[0023] In a preferred example, the catalytic reaction layer is composed of platinum nanoparticles.

[0024] In a preferred embodiment, the surface modification layer is obtained by silanization treatment.

[0025] In a preferred example, the silane compound used for the silanization treatment is selected from any one of vinyltrichlorosilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-glycidylpropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-chloropropyltrimethoxysilane.

[0026] In a preferred example, the biological enzyme sensing layer uses glucose oxidase or glucose dehydrogenase as the biological enzyme, and the thickness of the biological enzyme sensing layer is 2-15 μm.

[0027] In a preferred example, the hydrophilic and hydrophobic semipermeable membrane layer is composed of at least one material selected from the group consisting of polyvinyl pyridine, polyurethane, polyvinyl pyrrolidone and polyvinyl butyral.

[0028] In a preferred embodiment, the service life of the working electrode after implantation in the body is 1-28 days.

[0029] In a preferred embodiment, the steps include:

[0030] Step 1: performing surface treatment on the flexible base layer, including sequentially performing cleaning, aging and plasma treatment;

[0031] Step 2: forming a metal conductive layer on the treated surface of the flexible base layer;

[0032] Step 3: forming a catalytic reaction layer on the surface of the metal conductive layer by electroplating;

[0033] Step 4: performing surface modification treatment on the surface of the catalytic reaction layer to form a surface modification layer having a three-dimensional network structure;

[0034] Step 5: fix the biological enzyme on the surface modification layer by chemical cross-linking method to form a biological enzyme sensing layer, wherein the cross-linking temperature is 30-50° C. and the cross-linking time is 20-60 min;

[0035] Step 6: forming a hydrophilic and hydrophobic semipermeable membrane layer on the surface of the bio-enzyme sensing layer.

[0036] In a preferred embodiment, in step 1, the flexible base layer is cleaned with deionized water, an organic solvent or a combination thereof.

[0037] In a preferred embodiment, in step 2, the metal conductive layer is formed on the surface of the flexible base layer by screen printing, sputtering or vapor deposition process.

[0038] In a preferred embodiment, the electroplating process conditions in step 3 are: current density 10-50 mA / cm 2 , electroplating time 1-10min, electroplating solution temperature 30-70℃.

[0039] In a preferred embodiment, the step 4 adopts a dip coating method to perform surface silanization modification, which specifically includes pre-degreasing, degreasing, water washing and surface film forming steps, wherein:

[0040] The mass concentration of the silane compound is 0.1-10%, and the immersion treatment time is 10-60 minutes;

[0041] The surface film forming process is carried out by drying at 25-45°C, and the drying time is 20-90 minutes.

[0042] In a preferred embodiment, the cross-linking agent in step 5 is selected from any one of glutaraldehyde, adipaldehyde, chitosan, and ethylene carbonate, and the volume concentration of the cross-linking agent is 5-10 ml / dm 3 .

[0043] In a preferred embodiment, the semipermeable membrane layer is formed by spin coating or spray coating in step 6, the solvent used is tetrahydrofuran or chloroform, the mass concentration of the polymer material is 1-20%, and the following conditions are followed:

[0044] Film forming times 1-15 times;

[0045] The drying time after each film formation is 30-90 minutes.

[0046] The implementation methods of this application have the following technical effects:

[0047] The present application provides a working electrode for continuous glucose monitoring, which achieves continuous glucose monitoring with high sensitivity, high stability and high anti-interference by sequentially arranging a stacked structure of a flexible base layer, a metal conductive layer, a catalytic reaction layer, a surface modification layer, a biological enzyme sensing layer and a hydrophilic and hydrophobic semipermeable membrane layer.

[0048] The use of a flexible base layer with a thickness of 0.075-0.15mm and a width of 0.35-0.45mm can reduce the wearer's foreign body sensation and pain and improve wearing comfort.

[0049] The surface modification layer with a three-dimensional network structure formed on the surface of the catalytic reaction layer can not only improve the surface state of the catalytic reaction layer, but also enhance the fixation effect of the biological enzyme sensing layer and increase the enzyme fixation amount and stability.

[0050] The surface modification layer formed by silanization treatment can form a strong covalent bond with the surface of the catalytic reaction layer, and form a three-dimensional network structure through cross-linking between silane molecules, greatly enhancing the loading capacity and fixation stability of the biological enzyme.

[0051] The bio-enzyme sensing layer uses glucose oxidase or glucose dehydrogenase and is bonded to the surface modification layer through chemical cross-linking, ensuring sufficient enzyme quantity and enzyme activity to meet the continuous monitoring needs of up to 1-28 days.

[0052] Setting a 10-40μm thick hydrophilic and hydrophobic semipermeable membrane on the surface of the bio-enzyme sensing layer can effectively control the diffusion rate of glucose molecules, block other macromolecules and interfering substances, and greatly improve the selectivity and anti-interference ability of glucose monitoring.

[0053] The present application also provides a method for preparing the above-mentioned working electrode. By sequentially performing key steps such as base surface treatment, metal conductive layer preparation, catalytic reaction layer electroplating, surface silanization modification, bio-enzyme cross-linking fixation and semi-permeable membrane formation, the preparation parameters and performance of each functional layer can be precisely controlled, thereby ensuring the overall performance and batch stability of the working electrode.

[0054] The surface silanization modification is carried out by the dip coating method to form a uniform and dense silanization layer on the surface of the catalytic reaction layer. By controlling the concentration of the silane compound, the immersion time and the drying conditions, the three-dimensional network structure of the surface modification layer is optimized, providing a large number of bonding sites for the fixation of the biological enzyme.

[0055] By controlling the type, concentration, temperature and time of the cross-linking agent, efficient immobilization of the biological enzyme on the surface modified layer is achieved, and the activity and stability of the enzyme after immobilization are guaranteed, providing enzymatic support for long-term continuous monitoring.

[0056] The semipermeable membrane layer is prepared by spin coating or spray coating process. By optimizing the concentration of polymer materials, film forming times and drying time, a semipermeable membrane layer with stable performance, uniformity and density is obtained, achieving precise control of the diffusion of glucose molecules and the blocking of interferents.

[0057] In summary, the working electrode and preparation method of the present application achieve high-sensitivity, long-term, anti-interference continuous monitoring of glucose by rationally designing the electrode structure and optimizing the preparation process of each functional layer. It can be widely used in self-management and clinical diagnosis and treatment monitoring of chronic diseases such as diabetes, and has significant technical advantages and application value.

[0058] A large number of technical features are recorded in the specification of this application, which are distributed in various technical solutions. If all possible combinations of technical features of this application (i.e., technical solutions) are to be listed, the specification will be too long. In order to avoid this problem, the various technical features disclosed in the above-mentioned invention content of this application, the various technical features disclosed in the various embodiments and examples below, and the various technical features disclosed in the accompanying drawings can be freely combined with each other to form various new technical solutions (these technical solutions are all deemed to have been recorded in this specification), unless the combination of such technical features is technically infeasible. For example, in one example, feature A+B+C is disclosed, and in another example, feature A+B+D+E is disclosed, and features C and D are equivalent technical means that play the same role. Technically, only one can be used, and it is impossible to use them at the same time. Feature E can be combined with feature C technically. Then, the solution of A+B+C+D should not be deemed to have been recorded because it is technically infeasible, and the solution of A+B+C+E should be deemed to have been recorded. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is a schematic diagram of the structure of a working electrode for continuous glucose monitoring according to the first embodiment of the present application.

[0060] Figure 2 It is a schematic flow chart of a method for preparing a working electrode for continuous glucose monitoring according to the second embodiment of the present application. DETAILED DESCRIPTION

[0061] In the following description, many technical details are provided to help readers better understand the present application. However, those skilled in the art can understand that the technical solution claimed in the present application can be implemented even without these technical details and various changes and modifications based on the following embodiments.

[0062] Description of some concepts:

[0063] Continuous glucose monitoring (CGM): It is a technology that can continuously, automatically and in real time measure the glucose concentration in the interstitial fluid of the subcutaneous tissue. It usually uses an implantable electrochemical sensor, which can reflect the dynamic change trend of blood sugar and provide more comprehensive information for blood sugar management of diabetic patients.

[0064] Flexible base layer: refers to the electrode base layer made of flexible polymer materials, such as polyimide (PI), polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), polydimethylsiloxane (PDMS), etc., which can reduce the stimulation and damage of implantable electrodes to human tissues and improve wearing comfort.

[0065] Metal conductive layer: refers to a layer of metal film deposited on the surface of the flexible base layer, such as gold, graphite, silver, titanium, iridium, ruthenium, etc., which is used to conduct electrochemical signals. It is the core conductive component of the electrode and needs to have excellent conductivity and stability.

[0066] Catalytic reaction layer: refers to a layer of catalysts such as platinum nanoparticles modified on the surface of the metal conductive layer, which is used to electrocatalyze the oxidation reaction of glucose, accelerate electron transfer, and improve the current response sensitivity and specificity.

[0067] Surface modification layer: refers to the introduction of special chemical groups on the surface of the catalytic reaction layer or the formation of a three-dimensional porous structure. Usually, silanization treatment and other methods are used, such as vinyl trichlorosilane, γ-aminopropyl triethoxysilane, etc., to improve the physical and chemical properties of the electrode surface, increase the specific surface area, and provide a large number of active sites for the fixation of biological enzymes.

[0068] Bio-enzyme sensing layer: refers to the redox enzymes such as glucose oxidase (GOx) or glucose dehydrogenase (GDH) fixed on the surface modification layer, which converts the glucose concentration into a detectable electrochemical signal by utilizing the specific recognition reaction between the enzyme and glucose. It is the core functional layer for realizing biosensing.

[0069] Hydrophilic and hydrophobic semipermeable membrane: refers to a polymer membrane with both hydrophilic and hydrophobic properties, such as polyvinyl pyridine, polyurethane, etc., which is covered on the surface of the enzyme sensing layer. The selective permeability of the semipermeable membrane allows small molecules such as glucose to diffuse freely in and out, while blocking large molecular interferences such as blood cells and proteins, thereby improving the sensing selectivity and anti-interference ability.

[0070] Silanization treatment: refers to the method of chemically modifying the surface of a material using a silane coupling agent. Silane molecules form Si-OM bonds through dehydration condensation of their own siloxane groups with the surface of metal oxides, while exposing the organic functional groups at the other end to form a three-dimensional self-assembled film. Commonly used silanization agents include γ-aminopropyltriethoxysilane (APTES), vinyltrichlorosilane (VTCS), etc.

[0071] Chemical cross-linking fixation: refers to the method of using bifunctional reagents such as glutaraldehyde (GA) to covalently bond the enzyme molecules to the surface modification layer to form a stable enzyme immobilization modification layer. The cross-linking process is usually carried out under mild conditions to ensure that the conformation and activity of the enzyme molecules are not affected.

[0072] Current density: refers to the current per unit electrode area, measured in mA / cm 2 , is an important parameter for evaluating electrochemical reaction rate and sensor sensitivity. Optimizing electroplating process conditions such as current density, time, temperature, etc. is crucial to obtaining a catalytic reaction layer with excellent performance.

[0073] The following is a brief description of some of the innovative features of this application:

[0074] In response to the key technical problems existing in the clinical application of existing CGM products, including poor biocompatibility, low signal stability, weak enzyme fixation, poor selectivity and high cost, this application proposes a new working electrode and its preparation method, which achieves a comprehensive improvement in performance through innovative structural design and process optimization.

[0075] The core innovation of this application lies in the use of a carefully designed multilayer composite structure. First, a flexible base material of a specific size range (thickness 0.075-0.15mm, width 0.35-0.45mm) is selected to significantly improve the biocompatibility and wearing comfort of the electrode. Secondly, a unique three-dimensional network structure is formed on the surface of the catalytic reaction layer through silanization treatment. This structure is not only firmly bonded to the substrate through Si-OM covalent bonds, but also forms a large number of active sites through intermolecular cross-linking, thereby greatly improving the loading capacity and fixation stability of the enzyme.

[0076] In terms of performance control, the present application achieves effective regulation of the electron transfer channel and precise control of substrate diffusion by optimizing the interface structure between the surface modification layer and the catalytic layer, so that the electrode exhibits excellent sensitivity (1.9-3.1nA / mmol) and linearity (deviation 1.72-11.21%). At the same time, the hydrophilic and hydrophobic semipermeable membrane layer designed on the surface of the bio-enzyme sensing layer can selectively control the permeation of glucose molecules, effectively inhibit the influence of interfering substances, and the test recovery rate is stably maintained in the range of 92.7-105.5%.

[0077] It is particularly noteworthy that the synergistic effect of this multilayer structure significantly extends the service life of the electrode, which can work stably in vivo for 1-28 days, meeting the needs of clinical continuous monitoring. In terms of process, this application adopts conventional preparation methods such as dip coating, which has a simple process flow, is easy to control, has good batch stability and cost advantages, and lays the foundation for industrial production.

[0078] In summary, this application successfully achieves the comprehensive performance requirements of high sensitivity, low deviation, strong anti-interference and long life through innovative electrode structure design and optimized functional layer preparation process, provides a feasible solution to the technical bottlenecks of existing CGM products, and has significant technical innovation and practical value.

[0079] Compared with the prior art, the technical solution of this application has achieved significant improvements and innovations in the following aspects:

[0080] Advantages of the surface modification layer structure: Silanization treatment is used to form a unique three-dimensional network structure on the surface of the catalytic reaction layer, which not only forms a strong Si-OM covalent bond, but also forms a large number of active sites through cross-linking between silane molecules. Compared with materials such as m-phenylenediamine and chitosan used in comparative experiments, the surface modification layer of this application has higher chemical stability and biocompatibility. After testing, the biological enzyme activity (280-310nA / mmol) of this application is increased by about 50% compared with the control group (182-196nA / mmol), indicating that the modified layer significantly enhances the loading capacity and stability of the enzyme molecules.

[0081] Improved biocompatibility: By selecting flexible base materials and optimizing their thickness (0.075-0.15mm) and width (0.35-0.45mm) parameters, the electrode has good flexibility and fit. Experimental results show that this structural design can effectively reduce pain and foreign body sensation during implantation.

[0082] Improved measurement accuracy: This application achieves accurate detection of glucose molecules through the special structure of the surface modification layer and the selective control of the hydrophilic and hydrophobic semipermeable membrane. Test data show that the linear deviation is controlled within 11.21%, and the optimal value can reach 1.72%, which is significantly better than the 12.97-15.73% of the control group; the temperature response deviation is reduced to less than 1.5%, and the optimal value can reach 0.6%, while the control group is 3.0-4.2%, reflecting higher measurement accuracy.

[0083] Extended service life: The multi-layer composite structure design of the present application significantly improves the stability and durability of the electrode. The surface modification layer firmly fixes the biological enzyme through covalent bonding, and the semi-permeable membrane layer effectively blocks interfering substances. The synergistic effect enables the electrode to work stably and continuously in the body for 1-28 days.

[0084] Enhanced anti-interference performance: With a special surface modification structure and a selective semipermeable membrane, the working electrode of this application exhibits excellent anti-interference performance. The test results show that in the presence of interfering substances such as ascorbic acid (0.06g / L) and acetaminophen (0.02g / L), the anti-interference test recovery rate remained between 92.7-105.5%, while the control group was 112.1-116.5%, indicating that this application can more effectively suppress the influence of interfering substances.

[0085] Preparation process advantages: This application adopts the dip coating method for surface modification, chemical cross-linking and enzyme fixation, etc., which has the characteristics of simple process, convenient operation and controllable cost, which is conducive to industrial promotion.

[0086] The above technical effects have been verified through examples and comparative experiments, indicating that the present application has achieved significant improvements in various performance indicators and can effectively solve the key technical problems existing in existing CGM products.

[0087] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below in conjunction with the accompanying drawings.

[0088] The first embodiment of the present application relates to a working electrode for continuous glucose monitoring, and the process is as follows: Figure 1 As shown, including the following stacked in sequence:

[0089] Flexible base layer;

[0090] A metal conductive layer is disposed on the surface of the flexible base layer;

[0091] A catalytic reaction layer, disposed on the surface of the metal conductive layer, for catalyzing a glucose reaction;

[0092] A surface modification layer, formed on the surface of the catalytic reaction layer and presenting a three-dimensional network structure, is used to enhance the fixation of the biological enzyme;

[0093] A biological enzyme sensing layer is fixed on the surface of the surface modification layer by chemical bonding;

[0094] A hydrophilic and hydrophobic semipermeable membrane layer is disposed on the surface of the bio-enzyme sensing layer and is used to selectively control the permeation of glucose molecules;

[0095] The thickness of the flexible base layer is 0.075-0.15 mm, and the width is 0.35-0.45 mm; the thickness of the semi-permeable membrane layer is 10-40 μm.

[0096] Optionally, the surface modification layer is formed by silanization treatment.

[0097] Optionally, the flexible base layer is made of any one of polyimide (PI), polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), and polydimethylsiloxane (PDMS).

[0098] Optionally, the metal conductive layer is made of any one of gold, graphite, silver, titanium, iridium and ruthenium, and the thickness of the metal conductive layer is 2-30 μm.

[0099] Optionally, the catalytic reaction layer is composed of platinum nanoparticles.

[0100] Optionally, the surface modification layer is prepared by silanization treatment.

[0101] Optionally, the silane compound used for the silanization treatment is selected from any one of vinyl trichlorosilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-glycidylpropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, and γ-chloropropyl trimethoxysilane.

[0102] Optionally, the biological enzyme sensing layer uses glucose oxidase or glucose dehydrogenase as the biological enzyme, and the thickness of the biological enzyme sensing layer is 2-15 μm.

[0103] Optionally, the hydrophilic and hydrophobic semipermeable membrane layer is composed of at least one material selected from the group consisting of polyvinyl pyridine, polyurethane, polyvinyl pyrrolidone, and polyvinyl butyral.

[0104] Optionally, the working electrode has a service life of 1-28 days after implantation in vivo.

[0105] The second embodiment of the present application relates to a method for preparing a working electrode for continuous glucose monitoring, and the process is as follows: Figure 2 As shown, the following steps are included:

[0106] Step 100: performing surface treatment on the flexible base layer, including sequentially performing cleaning, aging and plasma treatment;

[0107] Step 200: forming a metal conductive layer on the treated surface of the flexible base layer;

[0108] Step 300: forming a catalytic reaction layer on the surface of the metal conductive layer by electroplating;

[0109] Step 400: performing surface modification treatment on the surface of the catalytic reaction layer to form a surface modification layer having a three-dimensional network structure;

[0110] Step 500: fix the biological enzyme on the surface modification layer by a chemical cross-linking method to form a biological enzyme sensing layer, wherein the cross-linking temperature is 30-50° C. and the cross-linking time is 20-60 min;

[0111] Step 600: forming a hydrophilic and hydrophobic semipermeable membrane layer on the surface of the biological enzyme sensing layer.

[0112] Optionally, in step 100, the flexible base layer is cleaned with deionized water, an organic solvent or a combination thereof.

[0113] Optionally, in step 200, the metal conductive layer is formed on the surface of the flexible base layer by screen printing, sputtering or vapor deposition process.

[0114] Optionally, the electroplating process conditions in step 300 are: current density 10-50 mA / cm 2, electroplating time 1-10min, electroplating solution temperature 30-70℃.

[0115] Optionally, the step 400 adopts a dip coating method to perform surface silanization modification, which specifically includes pre-degreasing, degreasing, water washing and surface film forming processes, wherein:

[0116] The mass concentration of the silane compound is 0.1-10%, and the immersion treatment time is 10-60 minutes;

[0117] The surface film forming process is carried out by drying at 25-45°C, and the drying time is 20-90 minutes.

[0118] Optionally, the cross-linking agent in step 500 is selected from any one of glutaraldehyde, adipaldehyde, chitosan, and ethylene carbonate, and the volume concentration of the cross-linking agent is 5-10 ml / dm 3 .

[0119] Optionally, the semi-permeable membrane layer is formed by spin coating or spray coating in step 600, the solvent used is tetrahydrofuran or chloroform, the mass concentration of the polymer material is 1-20%, and the process is carried out under the following conditions:

[0120] Film forming times: 1-15 times;

[0121] The drying time after each film formation is 30-90 minutes.

[0122] In order to better understand the technical solution of the present application, a specific example is provided below for illustration. The details listed in the example are mainly for ease of understanding and are not intended to limit the scope of protection of the present application.

[0123] This example provides a CGM working electrode and a preparation method thereof, comprising the following steps:

[0124] 1. Prepare a flexible substrate.

[0125] A metal layer is arranged on the flexible substrate, a catalytic reaction layer is arranged on the metal layer, a surface modification layer is deposited on the catalytic reaction layer, a biological enzyme sensing layer is fixed on the surface modification layer, and a semi-permeable membrane layer is coated on the biological enzyme sensing layer;

[0126] 2. Selection of substrate: A flexible substrate is used. Different from a rigid substrate, the human body has a stronger acceptance of a flexible substrate, and the foreign body sensation and pain sensation are lower when worn. It is preferred to use a substrate with a thickness of 0.075-0.15mm and a width of 0.35-0.45mm, which is a limit for the human body to accept pain. The pain sensation increases significantly when the value exceeds this value.

[0127] 3. The processing of the substrate includes cutting, cleaning, aging, plasma bombardment and other steps; after a simple cleaning, the substrate enters the aging step, the purpose is to allow the substrate to fully change in size in the front-end process, tend to be stable, and not affect the subsequent process. Then enter the plasma bombardment process: plasma is a form of matter. When charged particles move, they can cause the concentration of positive and negative charges to form an electric field; the movement of charges forms a magnetic field; the whole process has extremely strong thermal radiation and heat conduction; plasma collides with the surface of the substrate, knocking the pollutants off the surface to achieve the purpose of surface cleaning; plasma will also react chemically with the surface of the substrate to generate volatile substances and complete the treatment of pollutants; at the same time, the reaction of plasma causes changes to the microscopic level of the substrate surface, or produces etching and roughness, or forms a dense cross-linked layer, or introduces oxygen-containing polar groups, so that the surface hydrophilicity and adhesion are improved.

[0128] 4. The metal layer can be made of one of gold, graphite, silver, titanium, iridium, etc. The present application preferably uses gold as the metal layer. While having good conductivity, due to the characteristics of gold, its stability is also very excellent. It can inhibit the electrochemical reaction of the working electrode in the complex environment of the human body and ensure the accuracy of the output signal.

[0129] 5. The catalytic reaction layer is preferably platinum nanoparticles, which are attached to the metal layer by electroplating. The platinum catalytic layer prepared by electroplating is gray or black in color and has a porous surface. It can provide a larger surface area and accommodate more bio-enzymes during subsequent surface modification and bio-enzyme preparation. At the same time, the modified layer and the bio-enzyme sensing layer have enhanced adhesion and are not easy to fall off. The catalytic reaction layer is also prepared by silk screen printing or magnetic co-sputtering, but the surface of the platinum layer prepared by this method is smooth and silvery white in color. The subsequent process preparation is difficult and the effect is poor. The function of the catalytic reaction layer is also to catalyze the decomposition of H2O2 generated by the reaction between bio-enzymes and glucose; this product will cause the activity of the bio-enzyme to decrease, and the ability to monitor human blood sugar will decrease.

[0130] 6. The surface modification layer is preferably silanized. After hydrolysis, silane is rapidly adsorbed on the metal surface through the shrinkage reaction between its SiOH group and the MeOH group (M represents metal) on the metal surface; on the one hand, silane forms Si-O-Me covalent bonds on the metal interface. On the other hand, the remaining silane molecules form a silane film with a Si-O-Si three-dimensional network structure on the metal surface through the polycondensation reaction between the SiOH groups. After drying, the silane film is combined with the subsequent biological enzyme through a cross-linking reaction to form a strong chemical bond. This surface modification layer has an extremely positive auxiliary effect on the preparation of the subsequent biological enzyme sensing layer and can promote the fixation of the biological enzyme. At present, some working electrodes do not use a surface modification layer to assist in the fixation of the biological enzyme layer, which leads to the instability and easy shedding of the biological enzyme sensing layer, and the reduction of the working electrode life due to the insufficient amount of enzyme; there are also working electrodes using a three-dimensional network structure of a conductive polymer, but it also brings about the problem of reduced anti-interference performance, inaccurate current collection data, and excessive MAD deviation.

[0131] 7. The bio-enzyme sensing layer preferably uses glucose oxidase or glucose dehydrogenase, which have the same effect; preferably uses triethylamine, triethanolamine, glutaraldehyde, and the cross-linking dosage is 5-10ml / dm 3 The cross-linking temperature is 30-50℃, the cross-linking time is 20-60min, and the cross-linking fixation time and dosage cannot be too large.

[0132] 8. The semipermeable membrane preferably uses a biocompatible polymer with hydrophilicity and hydrophobicity, and its main functions are diffusion control, anti-interference and self-cleaning. Diffusion control can control the diffusion of glucose molecules, and anti-interference can prevent the diffusion of non-glucose substances. First, the tissue fluid or blood components entering the semipermeable membrane are reduced, and then the entry of other macromolecules other than glucose is prevented, while the accumulation of impurities and macromolecules on the membrane is removed to avoid affecting the service life of the working electrode. (The effect of self-cleaning can be found in the patent description of the self-cleaning membrane)

[0133] Further, optionally, the surface modification layer is selected from one of vinyl trichlorosilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy) silane, γ-glycidylpropyl-trimethoxysilane, γ-methacryloxypropyl-trimethoxysilane, γ-chloropropyl-trimethoxysilane, etc.;

[0134] Optionally, the base layer is a flexible material, which is one of polyimide (PI), polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), and polydimethylsiloxane (PDMS); the thickness of the base flexible material can be selected from one of 0.05mm, 0.075mm, 0.1mm, 0.125mm, 0.15mm, and 0.2mm; the width of the base flexible material can be between 0.3-0.5mm;

[0135] Optionally, the metal layer can be prepared by screen printing, welding, electrolytic deposition, etc. on the base layer, or by vapor deposition; the thickness of the metal layer can be between 2-30um, while saving costs, ensuring its conductivity and stability and the adhesion of the catalyst layer on its surface;

[0136] Optionally, the catalytic reaction layer can be prepared by electroplating, electrolysis, sputtering, screen printing, etc.;

[0137] Optionally, the surface modification layer needs to undergo pre-degreasing, degreasing, water washing, surface film formation and other processes; the surface modification layer surface film formation can be dried at 25-45°C for 20-90min;

[0138] Optionally, the biological enzyme used in the biological enzyme sensing layer is one of glucose oxidase and glucose dehydrogenase; the thickness of the biological enzyme sensing layer can be between 2-15 um, ensuring that the amount of enzyme can meet the needs of long-term continuous monitoring;

[0139] Optionally, the composition of the semipermeable membrane includes a biocompatible polymer with hydrophilicity and hydrophobicity, and the hydrophilic and hydrophobic polymer can be one or more of polyvinyl pyridine, polyurethane, polyvinyl pyrrolidone, and polyvinyl butyral; the solvent of the semipermeable membrane can be one of tetrachloroethylene and tetrahydrofuran, and the hydrophilic and hydrophobic polymers are blended therein;

[0140] Optionally, the film forming process of the semipermeable membrane can be one of coating, leaching, spin coating, and atmospheric deposition; the thickness of the semipermeable membrane can be between 10-40um, the number of film forming times can be stacked 1-15 times; the drying time between film forming is 30min-90min;

[0141] Optionally, the service life of the CGM working electrode is 1-28 days.

[0142] The first embodiment is a device embodiment corresponding to the present embodiment. The technical details in the first embodiment can be applied to the present embodiment, and the technical details in the present embodiment can also be applied to the first embodiment.

[0143] Test data analysis

[0144] In order to comprehensively evaluate the performance advantages of the working electrode of this application, a series of comparative experiments were conducted. The specific comparison scheme is as follows:

[0145] Comparative Example 1: m-phenylenediamine was used to prepare the surface modified layer, and the other process conditions were the same as those in Example 1;

[0146] Comparative Example 2: Chitosan was used to prepare the surface modification layer, and the other process conditions were the same as those in Example 1;

[0147] Comparative Example 3 was prepared by mixing m-phenylenediamine and chitosan, and the other process conditions were the same as those in Example 1.

[0148] Through detailed analysis of the test data, this application has shown significant advantages in various performance indicators:

[0149] 1.Mechanism of enhancing enzyme activity:

[0150] The surface modification layer of the present application forms a three-dimensional network structure through silanization treatment, which provides a large number of active sites for fixing biological enzymes. Experimental data show that the biological enzyme activity of the embodiment modified by silanization reaches 280-310nA / mmol, while the comparative example is only 182-196nA / mmol, an increase of about 50%. This is mainly due to:

[0151] * The Si-O-Si network formed by silanization has excellent mechanical strength and chemical stability

[0152] *The functional groups introduced on the surface form stable covalent bonds with the enzyme molecules

[0153] * The three-dimensional network structure provides a larger specific surface area and increases the enzyme loading capacity

[0154] In contrast, the conductive polymer structure in the comparative example is prone to degradation, and mainly relies on physical adsorption with enzyme molecules, resulting in a large loss of enzyme activity. This significant improvement in the activity of the biological enzyme directly extends the service life of the working electrode.

[0155] 2. Sensitivity control mechanism:

[0156] The present application achieves precise control of sensitivity within the ideal range of 1.9-3.1 nA / mmol, while the comparative example is higher (4.2-4.7 nA / mmol). This significant difference is due to:

[0157] *The uniform microporous structure formed by the silanization modified layer effectively regulates the diffusion rate of the substrate

[0158] *The stable interface formed between the surface modification layer and the catalytic layer provides a controllable electron transfer channel

[0159] *Directional fixation of biological enzymes improves the contact efficiency between enzymes and substrates

[0160] The conductive polymer structures used in the comparative examples often have problems such as uneven conductivity and unstable interface contact, making it difficult to achieve ideal sensitivity control. Accurate control of sensitivity ensures the reliability of the measurement results and is of great significance to improving the accuracy of monitoring data.

[0161] 3. Principle of linear deviation improvement:

[0162] The examples of the present application show excellent linearity (deviation 1.72-11.21%), which is significantly better than the comparative examples (12.97-15.73%). This improvement is attributed to:

[0163] *Uniform microenvironment provided by the surface modification layer ensures stable enzyme catalytic kinetics

[0164] *Selective control of the semi-permeable membrane layer to maintain a linear response range

[0165] *Synergistic effect of multi-layer structure to reduce signal fluctuation

[0166] The modified layer structure in the comparative example is not uniform, which easily leads to local reaction activity differences and affects the response linearity. The improvement of linear deviation significantly improves the measurement accuracy in different concentration ranges, making the electrode more suitable for clinical applications.

[0167] 4. Temperature response and anti-interference improvement mechanism:

[0168] This application shows excellent temperature stability (response deviation 0.6-1.5%) and anti-interference ability (recovery rate 92.7-105.5%). This performance improvement comes from:

[0169] *Silane network structure protects enzyme molecules and reduces temperature effects

[0170] *Selective shielding effect of surface modification layer to block interfering substances

[0171] *Multi-layer structure provides synergistic protection and a stable microenvironment

[0172] In contrast, the modified layer structure in the comparative example is relatively simple, lacking effective protection and selective shielding mechanisms, resulting in unsatisfactory temperature response deviation (3.0-4.2%) and anti-interference performance (recovery rate 112.1-116.5%). The improvement of temperature response and anti-interference makes the electrode more suitable for actual use environment and improves the reliability of monitoring results.

[0173] In summary, this application has achieved significant improvements in various performance indicators through a carefully designed surface modification layer structure. The unique three-dimensional network structure formed by silanization treatment not only provides an ideal bio-enzyme fixation environment, but also ensures the stability and selectivity of the electrode through multiple action mechanisms. These advantages have been fully verified in the experimental data, indicating that the technical solution of this application has obvious innovation and practical value, and provides important technical support for the development of a new generation of high-performance CGM products.

[0174] In order to further verify the comprehensive performance of the working electrode of the present application, a series of supplementary tests were conducted for the specific embodiment using γ-methacryloxypropyl-trimethoxysilane:

[0175] 1. Reliability Verification Test

[0176] The electrode performance was tested under the following conditions, with 10 samples in each group:

[0177] (1) Temperature cycle test: Tested at 25℃, 32℃, 37℃, and 40℃, with each temperature point maintained for 4 hours

[0178] -Linear deviation range: 1.72±0.31%

[0179] -Sensitivity range: 2.0±0.15nA / mmol

[0180] -Biological enzyme activity retention rate: ≥95%

[0181] (2) Mechanical bending test: 500 90° bending cycles and then tested

[0182] -No cracking of the flexible base

[0183] -The functional layers are complete in structure without delamination or peeling

[0184] -Performance index deviation <3%

[0185] (3) Wet-dry cycle test: PBS buffer immersion-natural drying cycle 50 times

[0186] - No significant degradation of the semipermeable membrane layer

[0187] -Biological enzyme activity retention rate>92%

[0188] - Sensitivity change <5%

[0189] 2. Repeatability test data

[0190] Three batches (10 in each batch) of samples were prepared continuously for performance testing. The results showed that the relative standard deviation (RSD) of the core performance indicators between batches was <5%, indicating that the process has good repeatability and controllability.

[0191] 3. Long-term stability test

[0192] Continuous monitoring for 28 days in a 37°C physiological environment, with performance tests performed every 3-4 days:

[0193] (1) Bioenzyme activity decay curve:

[0194] - Initial value: 310nA / mmol

[0195] -7 days: 298nA / mmol (maintenance rate 96%)

[0196] -14 days: 285nA / mmol (maintenance rate 92%)

[0197] -21 days: 273nA / mmol (maintenance rate 88%)

[0198] -28 days: 260nA / mmol (maintenance rate 84%)

[0199] (2) Changes in measurement accuracy:

[0200] -Sensitivity drift < 8%

[0201] - Linearity deviation is always < 5%

[0202] -Temperature response variation <2%

[0203] - Anti-interference performance remains within 90-105%

[0204] (3) Structural stability:

[0205] -The surface modification layer maintains a complete three-dimensional network structure

[0206] -The bio-enzyme layer is firmly fixed without obvious shedding

[0207] -The semi-permeable membrane layer has good permeability and no clogging

[0208] The above supplementary test data show that:

[0209] 1. The working electrode of this application has excellent environmental adaptability and mechanical stability, meeting various requirements under actual use conditions

[0210] 2. The preparation process has good repeatability and high batch consistency, which is conducive to industrial production

[0211] 3. Maintain stable performance indicators during 28 days of long-term use, which can meet the needs of clinical continuous monitoring

[0212] 4. The structure of each functional layer is stable, and the synergy is long-lasting and effective, ensuring reliable monitoring results

[0213] These results not only further confirm the reliability and practical value of this application in actual application, but also provide sufficient data support for clinical use. At the same time, the excellent batch stability and process controllability lay the foundation for the large-scale production of the product.

[0214] It should be noted that in the application documents of this patent, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "including one" do not exclude the existence of other identical elements in the process, method, article or device including the elements. In the application documents of this patent, if it is mentioned that an action is performed according to an element, it means that the action is performed at least according to the element, which includes two situations: performing the action only according to the element, and performing the action according to the element and other elements. Expressions such as multiple, multiple, and multiple include 2, 2 times, 2 kinds, and more than 2, more than 2 times, and more than 2 kinds.

[0215] All documents mentioned in this application are considered to be included in the disclosure of this application as a whole, so that they can be used as the basis for modification when necessary. In addition, it should be understood that after reading the above disclosure of this application, those skilled in the art can make various changes or modifications to this application, and these equivalent forms also fall within the scope of protection claimed in this application.

Claims

1. A working electrode for continuous glucose monitoring, characterized in that: Includes the following stacked: Flexible base layer; A metal conductive layer is disposed on the surface of the flexible base layer; A catalytic reaction layer, disposed on the surface of the metal conductive layer, for catalyzing a glucose reaction; A surface modification layer, formed on the surface of the catalytic reaction layer and presenting a three-dimensional network structure, is used to enhance the fixation of the biological enzyme; A biological enzyme sensing layer is fixed on the surface of the surface modification layer by chemical bonding; A hydrophilic and hydrophobic semipermeable membrane layer is disposed on the surface of the bio-enzyme sensing layer and is used to selectively control the permeation of glucose molecules; The thickness of the flexible base layer is 0.075-0.15 mm, and the width is 0.35-0.45 mm; the thickness of the semi-permeable membrane layer is 10-40 μm.

2. The working electrode according to claim 1, characterized in that The surface modification layer is formed by silanization treatment.

3. The working electrode according to claim 1, characterized in that The flexible base layer is made of any one of polyimide (PI), polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), and polydimethylsiloxane (PDMS).

4. The working electrode according to claim 1, characterized in that The metal conductive layer is made of any one of gold, graphite, silver, titanium, iridium and ruthenium, and the thickness of the metal conductive layer is 2-30 μm.

5. The working electrode according to claim 1, characterized in that The catalytic reaction layer is composed of platinum nanoparticles.

6. A method for preparing a working electrode as claimed in claim 1, characterized in that: The following steps are involved: Step 1: performing surface treatment on the flexible base layer, including sequentially performing cleaning, aging and plasma treatment; Step 2: forming a metal conductive layer on the treated surface of the flexible base layer; Step 3: forming a catalytic reaction layer on the surface of the metal conductive layer by electroplating; Step 4: performing surface modification treatment on the surface of the catalytic reaction layer to form a surface modification layer having a three-dimensional network structure; Step 5: fix the biological enzyme on the surface modification layer by chemical cross-linking method to form a biological enzyme sensing layer, wherein the cross-linking temperature is 30-50° C. and the cross-linking time is 20-60 min; Step 6: forming a hydrophilic and hydrophobic semipermeable membrane layer on the surface of the bio-enzyme sensing layer.

7. The preparation method according to claim 6, characterized in that: In the step 1, the flexible base layer is cleaned with deionized water, an organic solvent or a combination thereof.

8. The preparation method according to claim 6, characterized in that: In the step 2, the metal conductive layer is formed on the surface of the flexible base layer by screen printing, sputtering or vapor deposition process.

9. The preparation method according to claim 6, characterized in that: The electroplating process conditions in step 3 are: current density 10-50mA / cm 2 , electroplating time 1-10min, electroplating solution temperature 30-70℃.

10. The preparation method according to claim 6, characterized in that: The step 4 adopts the dip coating method to carry out surface silanization modification, which specifically includes pre-degreasing, degreasing, water washing and surface film forming processes, wherein: The mass concentration of the silane compound is 0.1-10%, and the immersion treatment time is 10-60 minutes; The surface film forming process is carried out by drying at 25-45°C, and the drying time is 20-90 minutes.

Citation Information

Patent Citations

  • Needle amperometric determination type glucose sensor for subcutaneous tissue real-time monitoring and manufacturing method thereof

    CN101530327A

  • Flexible electrochemical electrode, continuous glucose monitoring sensor and preparation method thereof

    CN105943058A

  • Working electrode of glucose monitoring probe, and manufacturing method of working electrode

    CN110057889A

  • Flexible sensor electrode preparation method, flexible sensor electrode and flexible sensor

    CN111007126A

  • Metal surface silanization treatment agent and treatment process thereof

    CN112708880A